A review of the current knowledge on Zeugodacus cucurbitae (Coquillett) (Diptera, Tephritidae) in Africa, with a list of species included in Zeugodacus - Meyer, M. de; Delatte, H.; Nwatawala, M.; Quilici, S.; Vayssières, Jean-François; Virgilio, M. (Pensoft Publishers, 2015)
This paper reviews all available information regarding the occurrence and biology of the melon fly, Zeugodacus cucurbitae (Coquillett), in the Afrotropical Region, including data on invasion history, distribution patterns, population genetics, host range, and interspecific competition. Although limited intraspecific variability has been observed within the region regarding the above mentioned aspects, there seems to be no indication that Zeugodacus cucurbitae represents a species complex. A checklist of all of the species included in Zeugodacus as recently proposed by Virgilio et al. (2015) is provided.